The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1128/cvi.00135-13
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Humoral Responses to the Plasmodium falciparum Vaccine Candidate EBA-175 Are Independent of the Erythrocyte Invasion Pathway

Abstract: dPlasmodium falciparum utilizes multiple ligand-receptor interactions for invasion. The invasion ligand EBA-175 is being developed as a major blood-stage vaccine candidate. EBA-175 mediates parasite invasion of host erythrocytes in a sialic acid-dependent manner through its binding to the erythrocyte receptor glycophorin A. In this study, we addressed the ability of naturally acquired human antibodies against the EBA-175 RII erythrocyte-binding domain to inhibit parasite invasion of ex vivo isolates, in relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 49 publications
(76 reference statements)
2
23
0
Order By: Relevance
“…RII binding to erythrocytes is inhibited by an anti-GpA antibody, α-2,3-sialyllactose and the neutralizing antibody R217 demonstrating a specific interaction with the host receptor. In addition, recombinant RII is recognized by sera from individuals living in endemic areas, and antibodies affinity purified by RII prevent parasite growth [18]. These studies further validate the potential for the use of recombinant RII described here in vaccine development and diagnostics to measure the immune response.…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…RII binding to erythrocytes is inhibited by an anti-GpA antibody, α-2,3-sialyllactose and the neutralizing antibody R217 demonstrating a specific interaction with the host receptor. In addition, recombinant RII is recognized by sera from individuals living in endemic areas, and antibodies affinity purified by RII prevent parasite growth [18]. These studies further validate the potential for the use of recombinant RII described here in vaccine development and diagnostics to measure the immune response.…”
Section: Discussionsupporting
confidence: 52%
“…Plasmodium falciparum Erythrocyte Binding Antigen of 175 kDa (PfEBA-1751) is a parasite protein ligand that binds to the erythrocyte receptor Glycophorin A during the blood-stage of the parasite life cycle [15]. PfEBA-175 is therefore an important antibody target and vaccine candidate [618]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although EBL ligands are functionally redundant, PfEBA-175 is an excellent vaccine candidate (44, 45) because it is a major invasion pathway (46) and antibodies that target PfEBA-175 inhibit parasite growth of multiple strains of P. falciparum , including those that use PfEBA-175-independent invasion pathways (47). Toward development of more efficacious vaccines, greater understanding of interactions between surface receptors and ligands is needed to better focus vaccine responses.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, EBA-175 RII (where cHABPs 1779 and 1783 are located) is recognised by antibodies in individuals having naturally acquired immunity in an age-dependent manner and inhibits invasion of P. falciparum clinical isolates to some degree (Okenu et al, 2000;El Sahly et al, 2010;Badiane et al, 2013;Irani et al, 2015). High-titre antibodies against EBA-175 RII are associated with protection from clinical malaria in children (Okenu et al, 2000;McCarra et al, 2011), although such association is not clear in some studies or has not been observed in groups having low incidence of disease (Osier et al, 2008;Richards et al, 2010) It has been suggested that EBA-175 RII polymorphism has shown immune selection aimed at maintaining genetic diversity in parasite populations.…”
Section: Antibody Reactivity From Individuals Living In Endemic Areasmentioning
confidence: 99%